Program Literasi Bahasa Arab Berbasis Teknologi dalam Meningkatkan Minat Belajar Siswa pada Kegiatan KPM di MI Nahdlatul Athfal - Alvin Ramdani; Enan (IKHTIAR: Jurnal Pengabdian Kepada Masyarakat, 2026)
Arabic language instruction at the Madrasah Ibtidaiyah level plays a crucial role in developing students’ basic linguistic competence and religious literacy. However, Arabic learning in primary Islamic schools often faces challenges, particularly low student learning interest caused by conventional teaching methods and limited use of instructional media. This article positions a technology-based Arabic literacy program as an alternative pedagogical approach to address this issue within the context of community service activities (Kuliah Pengabdian Masyarakat/KPM). The main question explored in this study is how the integration of technology-based literacy activities can enhance students’ interest in learning Arabic. The program was implemented through educational seminars and interactive learning activities utilizing digital media such as instructional videos, interactive slides, and Arabic vocabulary audio recordings. The discussion is based on qualitative observations of student participation, enthusiasm, and learning behavior during the program implementation at MI Nahdlatul Athfal. The results indicate that technology-based Arabic literacy activities significantly increased students’ enthusiasm, active participation, and confidence in practicing Arabic vocabulary. Students showed greater interest and positive attitudes toward Arabic learning when digital media were incorporated into the instructional process. These findings suggest that technology-based literacy programs can serve as an effective strategy to improve Arabic learning interest among Madrasah Ibtidaiyah students.